Disentangling the impacts of climate and human colonization on the flora and fauna of the Australian arid zone over the past 100 ka using stable isotopes in avian eggshell - Miller, Gifford; Fogel, M.; Magee, J.; Gagan, M. (Pergamon, 2016)
Throughout the Quaternary, the flora and fauna of Australia evolved and adapted to the high-amplitude, low- and high-frequency climate changes that characterized the ice-age cycles. However, during the last glacial cycle, between ~120 and 15 ka, unprecedented irreversible changes in flora and fauna occurred, and in that same interval modern humans established their first firm presence in the landscape. Disentangling the impacts of the first-order trend toward a colder, drier planet through the Late Quaternary from the impacts of human colonization has been challenging, from both the chronological and paleoenvironmental perspectives. We utilize the stable isotopes of carbon and oxygen preserved in near-continuous time series of Dromaius (emu) eggshell from five regions across Australia to provide independent reconstructions of ecosystem status and climate over the past 100 ka. Carbon isotopes are determined by the diet consumed by the female bird, whereas oxygen isotopes record the status of local moisture balance in the months prior to breeding. Together, d13C and d18O provide ecosystem status and climate from the same dated sample, reducing correlation uncertainties between proxies. Combined with recent improvements in the chronologies of Late Quaternary shorelines fringing inland lake basins and deflation during arid times, these data collectively reaffirm that Australia generally became increasingly, albeit irregularly, drier from the last interglaciation through to the last glacial maximum. Dromaius eggshell d18O documents peak aridity between 30 and 15 ka, but shows no evidence of exceptional climate change between 60 and 40 ka. In contrast, Dromaius d13Cdiet documents an irreversible loss of the majority of palatable summer-rainfall-related C4 grasses across the Australian arid zone between 50 and 45 ka, about the same time that the giant megafaunal bird, Genyornis, became extinct, and coincident with human dispersal across the continent. Our data indicate that changes unique to Australia occurred between 50 and 45 ka that led to a new climate-vegetation relationship and an overall reduction in effective moisture across much of the continent. The large summer-rainfall-dominated lakes of interior Australia failed to re-fill subsequently, despite a wide range of global climate states. A full explanation for the mechanisms behind these changes remains elusive, but they are almost certainly related to human agency. Plausible explanations include a change in fire regime resulting from human-lit fires, a change in fire regime following extinction of megafaunal browsers, and/or a threshold response to increasing aridity. Of these, the climate change explanation is least likely, given the lack of evidence for unprecedented aridity between 60 and 40 ka, and the successful adaptation of Australian ecosystems to 2.5 Ma of similar changes.